Numerical simulation of unsteady gunpowder combustion at a rapid rise in pressure on the basis of a conjugate combustion model - Krainov, Alexey Yu (Journal of engineering physics and thermophysics)
A physicomathematical model has been presented for solid propellant (gunpowder) combustion, in which account is taken of chemical reactions in the condensed and gaseous phases. Fourth-kind boundary conditions (conjugation conditions) were set on the combustion surface. The results of calculation of the N gunpowder combustion velocity at constant pressure agree well with the existing experimental data on the dependence of velocity on pressure. The results of numerical simulation of unsteady gunpowder combustion at a rapid rise in pressure have been presented. Quantitative data have been obtained on the deviation of the combustion velocity at a rapid rise in pressure from the steady values of the combustion velocity at constant pressure.